Silence Speaks Volume in Samuel Beckett's Waiting for Godot and Krapp's Last Tape - Neupane, Khagendra (Literary Studies, 2024)
The paper attempts to examine the deployment of silence as an intricate rhetorical device in Samuel Beckett's plays, Waiting for Godot and Krapp's Last Tape. In doing so, it seeks to interpret the rhetorical complexity of silence and its profound implications for the overall meanings of the plays. Simultaneously, the exploration of silence in Krapp's Last Tape extends beyond the surface, investigating its integral role in the protagonist's interactions with a tape recorder and its far-reaching implications for the play's temporal and mnemonic dimensions. The study underscores the profound interplay between silence and broader thematic elements in the plays, inviting a deeper exploration of Beckett's narrative techniques and paving the way for further investigations into the rhetoric of silence within literary discourse. Similarly, it examines the linguistic interplay between Vladimir and Estragon in Waiting for Godot, and Krapp's language evolution and the linguistic devices employed to convey his mental state in Krapp's Last Tape where language becomes an expression of existential angst. The analysis encompasses themes such as repetition, silence, absurdity, and non-linear narrative, shedding light on the impact of these linguistic elements on the portrayal of mental conditions.